Big Five dan Kesiapan Belajar Mandiri Mahasiswa pada masa Pandemi COVID-19 - Pratista Arya Satwika; Yudi Ariana Ariana; Fika Anggawati (Fakultas Psikologi Universitas Pancasila, 2022)
This study aims to analyze the influence of the Big Five personality dimensions on students' self-directed learning readiness during the COVID-19 pandemic. A total of 218 students who are running online learning are the subjects of this research. Data were collected using the Self-Directed Learning Readiness scale and the Big Five scale. Based on the results of the regression analysis, it is known that the five personality dimensions in the Big Five have a significant role in students' self-directed learning readiness during the COVID-19 pandemic. The five dimensions of the Big Five together contributed 58.7% to students' self-directed learning readiness during the Covid-19 pandemic. In addition, it was also found that partially conscientiousness personality is the variable that can most influence students' self-directed learning readiness, followed by openness to experience and agreeableness personality in the next order in influencing students' self-directed learning readiness during the Covid-19 pandemic. Meanwhile, the other two Big Five personality dimensions, neuroticism and extraversion, did not significantly affect students' self-directed learning readiness.